Răspuns :
(-0,75)×(+8/9)-5/4÷(-0,5)
=
=(-3/4)×(8/9)-5/4÷(-1/2)=
=-2/3-5/4× (-2)=
=-2/3+5/2=
=(-2*2+5*3)/6=11/6
=(-3/4)×(8/9)-5/4÷(-1/2)=
=-2/3-5/4× (-2)=
=-2/3+5/2=
=(-2*2+5*3)/6=11/6
(-0,75)×(+8/9)-5/4÷(-0,5) =
= - 75/100 × 8/9 - 5/4 : (- 5/10) =
= -15/20 × 8/9 - 5/4 × (-2) =
= - 120/180 + 10/4 =
= - 12/18 + 5/2 =
= - 12/18 + 5×9/2 =
= (- 12 + 45)/18 =
= 33/18 =
= 11/6
= - 75/100 × 8/9 - 5/4 : (- 5/10) =
= -15/20 × 8/9 - 5/4 × (-2) =
= - 120/180 + 10/4 =
= - 12/18 + 5/2 =
= - 12/18 + 5×9/2 =
= (- 12 + 45)/18 =
= 33/18 =
= 11/6